Atomic‐Scale Mechanisms of Nucleation and Stabilization in CuCrO2 and CuFeO2 Delafossite Thin Films on Al2O3 - Anna Scheid; Qi Song; Stephanie Ribet; Colin Ophus; Y. Eren Suyolcu; Darrell G. Schlom; Tobias Heil; Peter A. van Aken (Advanced Materials Interfaces, 2025)
Abstract Delafossite thin films exhibit a range of intriguing physical properties derived from their layered structure, which consists of alternating noble metal (A+) and (BO2−) sublayers in an ABO2 stoichiometry. The integration of these properties into functional devices requires the successful epitaxial growth of delafossites as thin films on appropriate substrates. Unfortunately, their unique lattice geometry complicates growth, as different delafossites display variable behavior on the same substrate, often unrelated to lattice mismatch. This suggests the presence of yet unidentified stabilization mechanisms that enable the selective growth of certain delafossites, allowing them to be grown either as films themselves or to be used as buffer layers for subsequent deposition. In this study, advanced scanning transmission electron microscopy (STEM) is employed to investigate the nucleation mechanisms governing the stable growth of Cu‐based delafossites on Al2O3, specifically CuCrO2 and CuFeO2 thin films synthesized via molecular‐beam epitaxy. These findings reveal that a combination of a misfit dislocation network at the interface and monolayer‐deep chemical intermixing effectively relieves lattice mismatch strain. This mechanism, which differs fundamentally from that observed in Pd‐based delafossites, provides key insights into the controlled epitaxy of delafossite materials.